2012
DOI: 10.6061/clinics/2012(07)11
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive positive-pressure ventilation in clinical practice at a large university-affiliated Brazilian hospital

Abstract: OBJECTIVES:To describe noninvasive positive-pressure ventilation use in intensive care unit clinical practice, factors associated with NPPV failure and the associated prognosis.METHODS:A prospective cohort study.RESULTS:Medical disorders (59%) and elective surgery (21%) were the main causes for admission to the intensive care unit. The main indications for the initiation of noninvasive positive-pressure ventilation were the following: post-extubation, acute respiratory failure and use as an adjunctive techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
1
5
0
5
Order By: Relevance
“…(17)(18)(19) The EI reasons noted by this research include the ARF and the decreased level of consciousness. Similar results were also found by Yamauchi et al (13) and Holland et al (10) , which emphasized these same points as the main causes of failure of NIV. Identification of predictive success or failure of NIV can both avoid unnecessary EI as to avoid a late EI and its complications.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…(17)(18)(19) The EI reasons noted by this research include the ARF and the decreased level of consciousness. Similar results were also found by Yamauchi et al (13) and Holland et al (10) , which emphasized these same points as the main causes of failure of NIV. Identification of predictive success or failure of NIV can both avoid unnecessary EI as to avoid a late EI and its complications.…”
Section: Discussionsupporting
confidence: 80%
“…In observational studies, Yamauchi et al (13) and Azevedo et al (7) found a significant relationship between the failure of NIV and lower levels of pH and worse prognosis, explicit through the longer length of stay in ICU and a higher mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of noninvasive ventilation after planned extubation is part of clinical practice worldwide. ( 1 - 4 , 15 ) In a study by Carlucci et al, ( 16 ) the rate of NIPPV in 52 ICUs was 8%. In our hospital, we estimated almost twice that rate (15%).…”
Section: Discussionmentioning
confidence: 99%
“…Yine Uzman merkezlerde, NPPV nin ARDS ye ilk etap tedavi olarak uygulanması sonucunda, tedavi edilen hastaların %54'ünde entübasyon uygulanmamıştır. Yalnızca SAPS II >34 çıkan ve 1 saatlik NPPV tedavisinden sonra PaO 2 /FiO 2 'si düzelmeyen hastalar entübasyona ihtiyacı var kabul edilmiş (9). Ayrıca akut solunum yetmezliği olan 64 hastada, NİPBV'nin invaziv MV kadar etkili olduğu ve NİPBV'nin uygulandığı hastaların YB'da kalış süresinin daha kısa ve ciddi komplikasyonların daha az olduğu belirtilmiştir (3).…”
Section: Discussionunclassified